2015
DOI: 10.1007/s00467-015-3141-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute focal bacterial nephritis, pyonephrosis and renal abscess in children

Abstract: AFBN, renal abscess and pyonephrosis should be suspected in children with severe presentation and urological history. Appropriate imaging is crucial for management planning. Prognosis is often guarded despite appropriate treatment. Based on the results of this study we propose a management algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 29 publications
1
28
0
20
Order By: Relevance
“…Additionally, Shinoda et al reviewed 34 cases of ALN, 18 cases of culture-negative bacteria, 5 cases of E. coli and 4 cases of E. faecalis 7. In other countries, single-centre studies have reported enterococcal ALN in 4 of the 25 cases in Germany,8 although none of the 21 cases in Greece9 and none of the 127 cases in Taiwan4 have reported such. These results suggest that a geographical difference may exist in causative organisms of ALN.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, Shinoda et al reviewed 34 cases of ALN, 18 cases of culture-negative bacteria, 5 cases of E. coli and 4 cases of E. faecalis 7. In other countries, single-centre studies have reported enterococcal ALN in 4 of the 25 cases in Germany,8 although none of the 21 cases in Greece9 and none of the 127 cases in Taiwan4 have reported such. These results suggest that a geographical difference may exist in causative organisms of ALN.…”
Section: Discussionmentioning
confidence: 97%
“…Por esto, es necesario llevar a cabo una adecuada evaluación diagnóstica (4,5,10). Aun así, como se demuestra en el caso clínico presentado, los diagnósticos diferenciales se pueden manifestar como estadios tempranos antes de la aparición del absceso (9).…”
Section: Discussionunclassified
“…En niños internados por infección urinaria, un 4% corresponde a esta entidad 3 y su asociación a uropatías en distintas series pediátricas varía entre 31% y 80%. [3][4] L a d e t e c c i ó n p r e c o z p e r m i t e e v i t a r complicaciones en el período agudo asociadas a septicemia, mayor hospitalización y mortalidad, de allí la importancia de la sospecha diagnóstica para confirmarla a través de imágenes. 4 Existen aislados reportes de la incidencia de cicatrices renales a largo plazo.…”
Section: Comentariounclassified
“…Hallazgos ecográficos de absceso renal: riñón izquierdo aumentado de volumen, hiperecogénico, con múltiples áreas hipoecoicas, heterogéneo con refuerzo acústico, con señal doppler negativa Figura 2. Imagen tomográfica de absceso renal: riñón izquierdo aumentado de volumen con cálices dilatados, con áreas de densidad atenuada que no captan contraste endovenoso los pacientes; aunque el 80% de estos niños eran urópatas, 3 en otras publicaciones, no se describió seguimiento a largo plazo. 4,5 La discusión en este paciente se centró en lo siguiente:…”
Section: Comentariounclassified
See 1 more Smart Citation